THE EFFECTIVENESS OF NURSE-LED WEIGHT MANAGEMENT AND OBESITY PREVENTION PROGRAMS - Alaatia Nafea Alrasheedi, Mona Salem Alshammari, Abdulaziz Naif Alanazi, Khaled Mufleh Alrashdi, Bader Ali Jehni, Fahd Salman Albathali, Ali Zugm Aljameeli, Maha Dham Alshammai; Halimah Mufleh Alrashedi, Amal Muteb Almutiri, Abdulaziz Naif Alanazi, Zahi Foriaan Alanazi, Eshraq Awad Al Johany, Zahra’a Abdulwahid Bin Haji (Chelonian Research Foundation, 2022)
Globally, the prevalence of childhood and teenage obesity is still rising. The healthcare workforce has made an effort, but there is a dearth of high-quality evidence that shows effective therapies for pediatric obesity. Given the size of the workforce and their increasing involvement in the prevention of chronic diseases, the role of nurses as main actors in the prevention of pediatric obesity has also received insufficient scientific attention. to assess the efficacy of nurse-led programs aimed at preventing overweight and obesity in children and adolescents. From the time of launch until March 2020, Medline, CINAHL, EMBASE, Cochrane (CENTRAL), ProQuest Central, and SCOPUS were searched. Nurse-led interventions employed education, counseling, and motivational interviewing to target behavior change in children's and teenagers' food and physical activity. They were complex, delivered in a variety of locations, and frequently involved parents. The majority of research did not find that nurse-led treatments prevented childhood and teenage overweight and obesity better than their comparator(s). Although they are practical, the efficacy of nurse-led treatments to prevent adolescent obesity has not yet been established. With appropriate training, nurses could contribute to the endeavor to prevent childhood obesity by more effectively utilizing current clinical and situational opportunities. Keywords: Review, nurse-led interventions, obesity, childhood, nutrition, feeding.